Pelatihan Peningkatan Tata Kelola Manajemen Inventaris Melalui Pembuatan Aplikasi di Pusksemas Sawah Besar Jakarta Pusat - Eka Miranda; Vieri Aska Juneio Sembiring; Ivan Surachman; Runna Aurelia (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The Sawah Besar Primary Health Care (Puskesmas) serves Central Jakarta. Among its services are an emergency room (ER), polyclinics in the morning and afternoon, maternity care, a laboratory, a pharmacy, and certificate processing. As a comprehensive healthcare center, it requires extensive inventory management of both medical and non-medical equipment. The Sawah Besar Primary Health Care used pen and paper to manually manage its medical and non-medical inventory. This method made it difficult to track incoming and outgoing goods and inventory, which led to inaccurate inventory counts. Patient care might be adversely affected by delays or errors in procurement. Puskesmas' operations required digital transformation via an inventory management application to streamline the medical and non-medical goods management process. The goal of this activity was to create a mobile application for managing inventory data for both medical and non-medical items. The implementation methods of this community service activity included field observation with partners, application development, outreach, and application use assistance, as well as evaluation and reporting. This activity could help primary health care improve inventory management by implementing a mobile application that allowed users to manage inventory data from anywhere and at any time.